Measuring and mapping the night sky brightness of Perth, Western Australia - Biggs, J.; Fouche, T.; Bilki, F.; Zadnik, Marjan (Wiley-Blackwell Publishing Ltd., 2012)
In order to study the light pollution produced in the city of Perth, Western Australia, we have used a hand-held sky brightness meter to measure the night sky brightness across the city. The data acquired facilitated the creation of a contour map of night sky brightness across the 2400 km2 area of the city – the first such map to be produced for a city. Importantly, this map was created using a methodology borrowed from the field of geophysics – the well proven and rigorous techniques of geostatistical analysis and modelling. A major finding of this study is the effect of land use on night sky brightness. By overlaying the night sky brightness map on to a suitably processed Landsat satellite image of Perth we found that locations near commercial and/or light industrial areas have a brighter night sky, whereas locations used for agriculture or having high vegetation coverage have a fainter night sky than surrounding areas. Urban areas have intermediate amounts of vegetation and are intermediate in brightness compared with the above-mentioned land uses. Regions with a higher density of major highways also appear to contribute to increased night sky brightness.When corrected for the effects of direct illumination from high buildings, we found that the night sky brightness in the central business district (CBD) is very close to that expected for a city of Perth’s population from modelling work and observations obtained in earlier studies. Given that our night sky brightness measurements in Perth over 2009 and 2010 are commensurate with that measured in Canadian cities over 30 years earlier implies that the various lighting systems employed in Perth (and probably most other cities) have not been optimised to minimize light pollution over that time. We also found that night sky brightness diminished with distance with an exponent of approximately -0.25 ± 0.02 from 3.5 to 10 km from the Perth CBD, a region characterized by urban and commercial land use. For distances from 10 out to about 40 km from the CBD the radial variation of night sky brightness steepens to have an exponent value of approximately -1.8 ± 0.2. This steepening is associated with land use because vegetation cover increases with further distance from the CBD.